KONFLIK SOSIAL DALAM NOVEL TANAH TABU KARYA ANINDITA, S THAYF - Hotmasari, Hotmasari; Nasution, Ismail; Marni, Silvia (Pendidikan Bahasa Indonesia, 2013)
The novel is a story that takes some union issues that are raised as sadness , joy , treachery , honesty , and other life problems . Social conflict is conflict that occurs as a result of human social contact with other people . Conflict can be found in all walks of life.The method used in this research is descriptive method . Descriptive method decomposes the data means in the form of words or pictures, not in the form of figures . The aim is to create a description , picture systematic , factual , and accurate statement of the facts, attributes and relationships anatar investigated phenomenon , so saw the quality or the quality of the object of scrutinyOutcomes Research ( 1 ) Social Conflict shape divided in two : (a ) Individual Conflict With Family Circle ( b ) Conflict Individuals With Social Circle . ( 2 ) Cause Social Conflict or matter giving rise to social conflicts . that the cause of social conflict can occur from a variety of factors namely economic factors , particularly poverty and cultural background differences . ( 3 ) Impact of Social Conflict is the result of social conflicts arising .Based on the results of research on social conflict in the novel Land Tabu Anindita work . S Thayf , it can be concluded that Mabel , Mace , and Leksi as protagonist experiencing social conflict that is individuals with conflicts within a family. While individual conflicts within society experienced by Mabel figures only.